Application of the microscopic method in cutaneous leishmania diagnosis - Mohammed Wael Daboul (Our Dermatology Online, 2011)
Introduction: Cutaneous leishmania is spreading fast. This study aims at developing the microscopic method to achieve a full detection of all positive cases of leishmania.Methods: 50 human cases have been studied by applying microscopic smears stained with Wright stain. Microscopic photos were taken for the presumed unfamiliar figures.Results: Mononuclear cells with tails are present at a rate of (98%). They are associated with Leishman Donovan (LD) bodies in 50% of the cases. The polygonal figures and the spherical forms are present at the same rate (60%) and are associated with LD bodies in 24% of the cases. The small promastigote like forms are seen at a rate of (76%) and are associated with LD bodies in 26% of the cases. The giant promastigotes like forms are present in (80% of the cases) and are associated with LD bodies in 28% of the cases. Candle flame forms are present in (40% of the cases) and are associated with the LD bodies in 21% of the cases.Discussion: It is applicable to use those discovered figures in diagnosing cutaneous leishmania.